STRUCTURAL AND FUNCTIONAL CHANGES IN THE TESTICLES AND EJACULATE OF INFERTILE MEN CAUSED BY EPIDEMIC PAROTITIS - Hrytsuliak, B.V.; Herashchenko, S.B.; Hrytsuliak, V.B.; Sluchyk, I.Y.; Glodan, O.Y.; Khallo, O.Y. (World of Medicine and Biology, 2024)
The purpose of the study was to establish the structural and functional changes in the testicles and ejaculate of 12 mature men with a history of epidemic parotitis. Ultrasound scanning and color ultrasound angiography of the testicles were performed in a clinical diagnostic center using a Siemens Sonoline G60S device (Siemens AW, Germany). Testicular volume and hemodynamic parameters were determined: peak arterial velocity, diastolic velocity, average blood flow velocity, and volumetric flow rate. In 7 testicular biopsies of infertile men with this pathology, taken in the urological department of the Regional Clinical Hospital of the Ivano-Frankivsk Regional Council, histostructural changes were studied. In the ejaculate, we studied the concentration of spermatozoa, their morphological forms, and motility according to generally accepted methods. According to ultrasound diagnostics, in infertile men with a history of mumps, the testicular volume decreased, on average, to 17.31±1.20 cm3 against 19.50±1.40 cm3 in control. Under these conditions, the peak arterial velocity in the testicular artery within the spermatic cord decreased to 14.90±1.20 cm/s against 19.30±1.46 cm/s, and the volumetric flow rate decreased to 14.20±1.15 ml/s against 16.50±1.20 ml/s in the control. In the examined histological micro preparations made from testicular biopsies of infertile men, the diameter of convoluted seminiferous tubules decreased compared to the control. Laboratory tests of ejaculate in men indicate a decrease in both its volume and the concentration of spermatozoa in it.